2012
DOI: 10.1186/1748-5908-7-98
|View full text |Cite
|
Sign up to set email alerts
|

Do guidelines influence the implementation of health programs? — Uganda’s experience

Abstract: BackgroundA guideline contains processes and procedures intended to guide health service delivery. However, the presence of guidelines may not guarantee their implementation, which may be a result of weaknesses in the development process. This study was undertaken to describe the processes of developing health planning, services management, and clinical guidelines within the health sector in Uganda, with the goal of understanding how these processes facilitate or abate the utility of guidelines.MethodsQualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 43 publications
0
45
0
Order By: Relevance
“…The content was developed in close collaboration with staff to assure that the guidelines are contextually achievable and easy to use . Contrary to the passive strategy often used to desseminate guidelines, PartoMa guidelines were actively applied at daily meetings and taught at seminars. It is likely that this reoccurring low‐dose training may have boosted guidelines use, particularly when considering the massive staff turnover.…”
Section: Discussionmentioning
confidence: 99%
“…The content was developed in close collaboration with staff to assure that the guidelines are contextually achievable and easy to use . Contrary to the passive strategy often used to desseminate guidelines, PartoMa guidelines were actively applied at daily meetings and taught at seminars. It is likely that this reoccurring low‐dose training may have boosted guidelines use, particularly when considering the massive staff turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, review of Uganda’s health sector guidelines concluded that low income countries face multiple barriers in conducting guidelines modification processes [18]. It is therefore warranted that the central development process of international evidence-based guidelines targeting low resource settings involve end users already in the initial phases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Global Fund addressed HIV TB and malaria, US president's Emergency Plan for AIDS Relief addressed HIV/AIDS; Stop TB focused on TB; the malaria partnership focused on malaria and the global alliance for vaccine initiative focused on Immunisation. GHI demanded new strategic plans and guidelines despite the existence of national health sector strategic plans (HSSP) . This resulted in what was perceived as contradictions in strategic planning frameworks partly stemming from funding conditionalities, different time frames, and re‐verticalisation of planning, management and monitoring, and evaluation systems …”
Section: Introductionmentioning
confidence: 99%